Exploring the incidence and influencing factors of postoperative nausea and vomiting after laparoscopic bariatric surgery: a protocol for a retrospective observational study - Juan Tan; Qiang Fu; Lin Tan; Haibei Liu (BMJ Open)
Introduction The global prevalence of obesity and its associated comorbidities is rising, with bariatric surgery emerging as a highly efficacious intervention for obese patients. Postoperative nausea and vomiting (PONV) is a common complication following bariatric surgery, with a standardised protocol for its prevention and management yet to be established. This study aims to determine the incidence and the influencing factors of PONV following various types of bariatric surgeries, thereby facilitating the targeted prevention strategies.Methods and analysis This retrospective, single-centre observational study will be conducted at the Third People’s Hospital of Chengdu, with an expected enrolment of 2500 patients who have undergone laparoscopic bariatric surgery from December 2019 to April 2024. The study aims to collect data regarding the incidence of PONV and analyse the potential risk and protective factors associated with its development in this patient population.Ethics and dissemination The study has been approved by the ethics committees of the Third People’s Hospital of Chengdu. Given the retrospective nature of the study, informed consent was waived by the ethics committee, and all patient data were anonymised to safeguard privacy prior to the study authors’ visit. The results of this study will be presented at various academic and healthcare conferences, spanning local to international levels and will also be submitted for publication in reputable, peer-reviewed journals.Trial registration number This study has been registered with the Chinese Clinical Trial Register (ChiCTR) under registration number ChiCTR2400088738.